Expression of RNA virus proteins by RNA polymerase II dependent expression plasmids is hindered at multiple steps - Überla Klaus; Kuate Seraphin; Stefanou Daniela; Ternette Nicola; Grunwald Thomas (Virology Journal, 2007)
Abstract Background Proteins of human and animal viruses are frequently expressed from RNA polymerase II dependent expression cassettes to study protein function and to develop gene-based vaccines. Initial attempts to express the G protein of vesicular stomatitis virus (VSV) and the F protein of respiratory syncytial virus (RSV) by eukaryotic promoters revealed restrictions at several steps of gene expression. Results Insertion of an intron flanked by exonic sequences 5'-terminal to the open reading frames (ORF) of VSV-G and RSV-F led to detectable cytoplasmic mRNA levels of both genes. While the exonic sequences were sufficient to stabilise the VSV-G mRNA, cytoplasmic mRNA levels of RSV-F were dependent on the presence of a functional intron. Cytoplasmic VSV-G mRNA levels led to readily detectable levels of VSV-G protein, whereas RSV-F protein expression remained undetectable. However, RSV-F expression was observed after mutating two of four consensus sites for polyadenylation present in the RSV-F ORF. Expression levels could be further enhanced by codon optimisation. Conclusion Insufficient cytoplasmic mRNA levels and premature polyadenylation prevent expression of RSV-F by RNA polymerase II dependent expression plasmids. Since RSV replicates in the cytoplasm, the presence of premature polyadenylation sites and elements leading to nuclear instability should not interfere with RSV-F expression during virus replication. The molecular mechanisms responsible for the destabilisation of the RSV-F and VSV-G mRNAs and the different requirements for their rescue by insertion of an intron remain to be defined.